Asymmetric inheritance of spindle microtubule-organizing centres preserves replicative lifespan - Manzano-López, Javier; Matellán, Laura; Álvarez-Llamas, Alejandra; Blanco-Mira, José Carlos; Monje-Casas, Fernando (Nature cell biology, 2019)
The differential distribution of the microtubule-organizing centres (MTOCs) that orchestrate spindle formation during cell division is a fascinating phenomenon originally described in Saccharomyces cerevisiae and later found to be conserved during stem cell divisions in organisms ranging from Drosophila to humans. Whether predetermined MTOC inheritance patterns fulfil any biological function is however unknown. Using a genetically designed S. cerevisiae strain that displays a constitutively inverted MTOC fate, we demonstrate that the asymmetric segregation of these structures is critical to ensure normal levels of the Sir2 sirtuin and correct localization of the mitochondrial inheritance regulator Mfb1, and therefore to properly distribute functional mitochondria and protein aggregates between the mother and daughter cells. Consequently, interfering with this process severely accelerates cellular ageing. Yeast cells segregate the old spindle pole body into the bud. Manzano-López et al. report that inverted segregation accelerates ageing due to aberrant partition of protein aggregates and damaged mitochondria.